Kansas farm management association dairy cow herd enterprise management analysis - DeLano, F. D.; Langemeier, Michael R. (Kansas Agricultural Experiment Station, 2011)
Actual dairy cow herd enterprise records from Kansas Farm Management Association farms over the past 4 years have shown an increase in returns over variable costs from $17,900 to $23,300 per farm for a 100-cow dairy herd in favor of herds with higher milk-producing cows. Cost per hundred weight of milk produced per cow decreased for the higher-producing herds compared with lower-producing herds, even though total cost per cow increased. In 1992, for every extra $1.00 spent on feed and other variable costs, the higher producing herds earned $1.71. This was a 71% return per dollar invested.
Typo of author's name M. L. Langemeier; should be M. R. Langemeier.
Keywords: Dairy; Economics; Management